EPIDEMIOLOGICAL PROFILE OF HIGH-RISK PREGNANT WOMEN - Lediana Dalla Costa; Caroline Cales Cura; Alessandro Rodrigues Perondi; Vivian Francielle França; Durcelina Schiavoni Bortoloti (Universidade Federal do Paraná, 2016)
The objective in this study was to outline the epidemiological profile of high-risk pregnant women attended at the Instituto da Mulher of the Municipal Health Department in the city of Francisco Beltrão, Brazil. Sixty-one patient histories were assessed between January and June 2015. It was verified that 82% (N=50) of the pregnant women were between 15 and 35 years of age; 47.5% (N=29) had finished secondary education; 52.5% (N=32) were married; 62.3% (N=38) were white; 88.5% (N=54) had family antecedents of chronic illness, 63.9% (N=39) related to arterial hypertension; 82% (N=50) had personal antecedents, with 52.5% (N=32) of urinary infection cases; 70.5% (N=43) were multipara. The high-risk pregnancy evolved to caesarean sections in 80.3% (N=49) of the cases. This study produced important information about the profile of this population, which allows the professionals involved in care delivery to high-risk pregnant women to play a fundamental role in the reduction of maternal mortality. In conclusion, the profile of these high-risk pregnant women seemingly does not differ from the reality in other Brazilian cities, mainly concerning hypertension as an important factor of family and personal antecedents and current prevalence.